Технологія відеореферування на основі кластеризації для інформаційного пошуку - Столбовий, М. І. (ХНУРЕ, 2019)
Дисертація присвячена розвитку технологій інформаційного пошуку в плані розробки моделей і методів сегментації і кластеризації відеоданих для динамічного відеореферування. Введено методи і моделі виявлення змін властивостей векторних і матричних нестаціонарних зашумлених сигналів на основі ансамблю адаптивних моделей з власними алгоритмами ідентифікації з різною глибиною пам’яті, on-line процедури нечіткої кластеризації, що забезпечують часову сегментацію як для повільних, так і стрибкоподібних змін змісту відео. На основі гібридизації ієрархічного агломеративного і нечіткого, заснованого на центрах ваги, підходів для динамічного відеореферуровання запропонований метод кластеризації багатовимірних часових рядів різної довжини в умовах невідомої кількості класів і можливості їх взаємного перетину. Для відеореферування запропонована кластеризація послідовностей відеоданих, яка заснована на використанні модифікованої ітеративної динамічної часової деформації і подальшої кластеризації редукованих часових рядів на основі матричної нечіткої кластеризації на базі гармонійних k -середніх. Результати теоретико-експериментальних досліджень реалізовані і впро-ваджені у вигляді прикладних і дослідницьких програмних комплексів. Enormous volumes of having different modalities video produce a barrier to many information technology activities. There exist numberless semantic concepts that are very difficult or even impossible to extract automatically. Video abstraction is a mechanism for producing a short summary of a whole video and it is a significant part of such applications as video indexing, browsing and semantic retrieval. Recog-nizing the usefulness of video abstraction within the broader field of multimedia content management, it should be emphasized that the focus is on video temporal segmentation and clustering. One of central problems regarding the content based retrieval with queries ad exemplum concerns with image sequences un-derstanding and ranking extracted skims according to the relevance degree to the user query. Video excerpt is identified as important, interesting, or exciting if it is an event with a specific semantic label, or captures the attention of the viewer. In addi-tion, sequences are essential if they may be associated with some patterns, or have specific temporal and spatial attributes.Effective abstraction of video contents can be expressed as a sequence of sta-tionary representative images called keyframes or moving images (video skims, mov-ing storyboard or summary sequence). If static video abstraction which based on keyframes is sufficiently well ex-plored, then dynamic summarization remains an unresolved problem. At the same time, dynamic summarization has a number of advantages over a keyframe set, among which potentially enhance both the expressiveness and information of the ab-stracts should be indicated and, as a consequence, possibilities to find more relevant information by video search engine become more obvious. In the thesis the actual scientific and practical problem of video data segmenta-tion and clustering models and methods for dynamic video summarization has been solved with the aim of temporal visual information retrieval technologies develop-ment. Based on trends of video streams abstraction evolution in order to increase the content relevance of information retrieval, the promising perspectives of dynamic video summarization are established. It is established that the known methods of segmentation, clustering and summarization of video sequences do not fully meet modern requirements and require substantial improvement. Fast change detection of vector and matrix nonstationary noise signal proper-ties based on an ensemble of adaptive models with their own identification algo-rithms with different memory depths creates prerequisites for the segmentation of video sequences taking into consideration the structural and polysemy properties of video streams separate parts. Introduced on-line fuzzy clustering procedures allow solving the problem of detecting discrepancies in multidimensional time series for both smoothed and abrupt changes in video content, which ensures high relevance of video streams temporal analysis. Change detection of various lengths multidimensional sequences on the basis of Iterative Dynamic Time Warping analysis, which is associated with adaptive re-duction of time series, makes it possible to obtain modifications of clustering algo-rithms for vector and matrix time sequences with aim of summarizing pertinences growth. The proposed clustering method for multidimensional time series of different lengths under an unknown classes number and the possibilities of their mutual inter-section based on hybridization of hierarchical agglomerative and fuzzy centroid-based approaches using Levenshtein metric provides the opportunities of a valid search with complex summarizing queries. The proposed approaches to adaptive matrix model parameters alignment and matrix sequence change detection provide reducing the gap between formal and se-mantic relevance due to the fact that fragments resulting from arbitrary spatial convo-lution can characterize the neighborhoods of points that represent visual attention. The introduced technique for video sequences clustering with subsequent grouping of reducible time series based on harmonic-average fuzzy clustering has a simple computational model and increased stability to local time deformations. For the detection of spatial and temporal events in video streams with the aim of semantic summarization of video, the clustering of temporal sequences with dif-ferent lengths using representatives and the dynamic transformation of the time scale seems promising from a practical point of view. Video sequences segmentation and clustering methods were implemented software and have been applied for control large collections of unstructured dynamic information and context-sensitive search with requests ‘ad exemplum’, that is con-firmed by relevant acts.
Keywords: відео; відеореферування; багатовимірні часові ряди; сегментація; кластеризація; video; video retrieval; multidimensional time series; segmentation; clustering